O dwóch nagrobkach Mikołaja Tomickiego - Nowakowski, Piotr (Acta Universitatis Lodziensis. Folia Archaeologica, 2004)
Two tombstones of the ensign of Poznań Nicolas Tomicki, of the Łodzia clan, are not numerous cases when the same person appears in iconography more than once. It enables the comparison of the images as well as their analysis not only from the portrait point of view, but also the correlation between dress or armament details. In the article the results of an analysis of both Nicolaus Tomicki’s tombstones are presented; the aim of the analysis is to show the armament in the images. The first tombstone comes from the turn of the 15th century, so it must have been made for the ensign and under his supervision. Foundation of the second tombstone, from 1524, is the work of his son Nicolaus – the archbishop of Cracow and Poznań as well as of the secretary of Sigismund the Old – Peter Tomicki. Both sets of armament considerably differ from each other not only in respect of the suite of elements, but also a variety of their ornamentation. It can be presumed that Peter Tomicki considered the first tombstone of his father too simple for an ancestor of a church notable and the king’s secretary and that is why he founded another tombstone, with a changed image and an accompanying inscription. Certainly the armament showed on the earlier tombstone can be regarded as materialised representation of how, according to the bishop, a powerful knight, who follows the changes of battlefield, or maybe only knights’ fashion, should look like. Only few elements of the armament, on the grounds of comparison with the older tombstone, can be included to authentic components of the armament of Nicolaus Tomicki.